Intermolecular Chirality Modulation of Binaphthalene-Bridged Bisporphyrins With Chiral Diamines - Lu, Wenxin; Gong, Lei; Su, Chaorui; Wang, Qibao; Ling, Qing; Wang, Peng; Qi, Dongdong; Bian, Yongzhong (Frontiers in Chemistry, 2021)
A new pair of 2,2ʹ-diamino-1,1ʹ-binaphthyl bridged bisporphyrins, (R)-/(S)-H, were synthesized to examine their supramolecular interactions with a pair of chiral diamines ((R)-/(S)-PPDA) by using UV-Vis absorption, fluorescence and NMR titrations. The spectroscopic titrations indicated that sandwich-type 1:1 complexes were formed at low guest concentration and then transformed to 1:2 open complexes at high guest concentration. The binding processes afforded sensitive CD spectral changes in response to the stereostructure of chiral diamines, and the final CD signs are primarily decided by the chiral diamine guests. The present results suggest the chiral bisporphyrin hosts are promising for chiral optical sensing.